Metal hydrides studied in gas discharge tube. (May 2016) - Bozhinova, I; Kolev, S.; Popov, Tsv.; Pashov, A.; Dimitrova, M.
Abstract: A novel construction of gas discharge tube has been tested for production of high densities of metal hydrydes. Its performance turned out to be comparable with the existing sources of the same type and even better. First results of the tests on NiH are reported and critically analysed. Plans for future modifiaction of the construction and application of the tube are discussed.